The long non-coding RNA NEAT1 is elevated in polyglutamine repeat expansion diseases and protects from disease gene-dependent toxicities. (19th September 2018) - Cheng, Congsheng; Spengler, Ryan M; Keiser, Megan S; Monteys, Alejandro Mas; Rieders, Julianne M; Ramachandran, Shyam; Davidson, Beverly L
Abstract: Polyglutamine (polyQ) repeat diseases are a class of neurodegenerative disorders caused by CAG-repeat expansion. There are diverse cellular mechanisms behind the pathogenesis of polyQ disorders, including transcriptional dysregulation. Interestingly, we find that levels of the long isoform of nuclear paraspeckle assembly transcript 1 ( Neat1L ) are elevated in the brains of mouse models of spinocerebellar ataxia types 1, 2, 7 and Huntington's disease (HD). Neat1L was also elevated in differentiated striatal neurons derived from HD knock-in mice and in HD patient brains. The elevation was mutant Huntingtin (mHTT) dependent, as knockdown of mHTT in vitro and in vivo restored Neat1L to normal levels. In additional studies, we found that Neat1L is repressed by methyl CpG binding protein 2 (MeCP2) by RNA-protein interaction but not by occupancy of MeCP2 at its promoter. We also found that NEAT1L overexpression protects from mHTT-induced cytotoxicity, while reducing it enhanced mHTT-dependent toxicity. Gene set enrichment analysis of previously published RNA sequencing data from mouse embryonic fibroblasts and cells derived from HD patients shows that loss of NEAT1L impairs multiple cellular functions, including pathways involved in cell proliferation and development. Intriguingly, the genes dysregulated in HD human brain samples overlap with pathways affected by a reduction in NEAT1, confirming the correlation of NEAT1L and HD-induced perturbations. Cumulatively, the role of NEAT1L in polyQ disease model systems and human tissues suggests that it may play a protective role in CAG-repeat expansion diseases.